Development of Intelligent Tutoring System Model in the Learning System of the Indonesian National Armed Forces Completed with Bibliometric Analysis - Kurniawan, Bobi; Meyliana, M.; Warnars, Harco Leslie Hendric Spits; Suharjo, Bambang (ASEAN Journal of Science and Engineering, 2024)
This research aims to develop and design an Intelligent Tutoring System (ITS) model to improve the efficiency and adaptability of the learning process using technology based on student personalization. This study employs a systematic literature review method, as well as bibliometric analysis and visualization using the VOSviewer application. We collected data from several well-known article databases. The results showed an intelligent tutoring system model to be connected to five components and 22 sub-components. These components consist of a student model, a pedagogical model, an interface model, a tutor model, and a domain model. Thus, these components and sub-components produce a responsive student model that can be used to develop a learning system within the Indonesian National Armed Forces. The responsive student model not only assesses students' visual, auditory, or kinesthetic learning styles but also gauges their emotions or concentration levels during the learning process. This development not only increases learning effectiveness but also improves student learning experiences and supports adaptive and sustainable academic growth.